Performance ratio of the PLTS system for blue swimming crab handling on the boat in field testing and PVsyst software simulation - Kuncoro Ari; Agus Setiawan Ahmad; Natsir Moh; Sasmita Suparman; Wisnugroho Susilo; Setiyobudi Nanang; Zarochman; Hufiadi; Suryo Sukoraharjo Sri; Wassahua Zainal; Muji Permana Sofiyan; Nurbaya Sari Rodiah; et al. (BIO Web of Conferences)
On the northern coast of Java, some fishermen catch the blue swimming crab (BSC) for more than one day, which risks damaging the BSC; therefore, the fishermen will perform the initial steps of steaming and cold storage on the boat. As an alternative initial process, fishermen can use electrical devices for BSC processing by converting solar energy into electrical energy using a solar power plant (PLTS). We have designed an off-grid PLTS for the initial processing of BSC and lighting. This research aims to determine the performance ratio (PR) of the off-grid PLTS for the initial processing of the BSC compared to simulations using PVsyst software. The method used was qualitative, testing the off-grid PLTS on a boat in Rembang and comparing the PR with the simulation results from the PVsyst software. The off-grid PLTS system exhibited a PR of 0.379, whereas the simulation result was 0.710. The economic analysis indicated that the off-grid PLTS system cost for every kilowatt-hour (kWh) of electricity generated by the PLTS system is IDR 19,497,90. The testing results of the off-grid PLTS system showed low PR, but we hope fishermen can use this system for the initial handling of BSC on the boats.